LEGAL REVIEW OF PROCUREMENT AUTHORIZATION OF THE IMPORTED FRESH FOOD, FRUIT AND VEGETABLE - Haerani, Yeni; Nurcahyo, Edy (Jurnal Hukum Volkgeist, 2019)
Fresh food products imported fruits and vegetables in circulation that do not meet the requirements in accordance with statutory regulations can endanger human safety because food security is not guaranteed. The existence of a marketing authorization and supervision of imported fresh fruit and vegetable food products is needed to maintain food security. The research method used is the normative legal research method that is the legal research method of literature with the method used to examine existing library materials related to the object examined by the regulatory approach (statue approach). The results showed that before the imported fresh fruits & vegetables food products were circulated, they had to go through several quarantine measures or inspections. After passing the test, they would get a distribution permit for fresh food products along with the registration number on the imported fruit & vegetable label. If the distribution permit for fresh food products is ignored by business actors, they will be subject to criminal and administrative sanctions. The purpose of supervision is to provide protection to consumers and prevent the circulation of imported fresh fruit and vegetable food products that can endanger consumers' health.   Keywords: Distribution Permit; Fresh Fruit and Vegetable Products; Consumer Protection